Effect of different custom-made foot orthotics on foot joint stiffness in individuals with structural hallux limitus: A quasi-experimental study - Martínez-Rico, Magdalena; Gijón-Noguerón, Gabriel; Ortega-Ávila, Ana Belén; Roche-Seruendo, Luis Enrique; Climent-Pedrosa, Ana; Deschamps, Kevin; Sanchis-Sales, Enrique (Elsevier, 2025)
Background: Normal dorsiflexion of the first metatarsophalangeal joint during dynamic activities is critical for effective propulsion. Therapeutic foot orthotics may address the pathomechanical loading and joint kinematics issues faced by this population. This study aims to evaluate the effect of two different types of Custom-made foot orthosis compared to shod condition on the stiffness of the rearfoot, midfoot, and 1st metatarsophalangeal joint during walking in patients with Structural Hallux Limitus. Methods: This quasi-experimental study used a repeated-measures design with a single cohort. 24 participants with structural hallux limitus were sampled. Two custom-made Foot Orthotics – a cut-out and an anterior forefoot stabiliser element – were compared under three conditions using minimalist SAGURO neoprene shoes: shod, shod with cut-out custom-made foot orthosis, and shod with anterior forefoot stabiliser element foot orthosis. Kinematic data were captured using a modified Bruening model. We examined the variable stiffness (quantified in Nm/Kg/rad). Findings: Significant differences were found in dynamic stiffness only between Anterior forefoot stabiliser element custom-made foot orthosis, and the patient shod during the propulsion phase at the 1st Meta- tarsophalangeal joint (R2 = 0,07 p = 0.027) and a difference of 0,86 Nm/kg/rad. No significant differences were observed for dynamic stiffness in any other phase of the stance period across all conditions. Interpretation: The Anterior forefoot stabiliser element, in particular, significantly increases the stiffness of the 1st Metatarsophalangeal joint compared to walking shod.
Keywords: Aparato locomotor -- Enfermedades; Pies -- Lesiones y heridas -- Tratamiento; Pies -- Anomalías y malformaciones; Custom-made foot orthotics; Joint stiffness; Structural hallux limitus